2023
DOI: 10.1007/s12665-023-10795-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical formation mechanism of mineral springs in Changbai Mountain (China)

Abstract: The funding body has funded sample collection tests and data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Gibbs diagrams and rock end-member element ratio diagrams can be used to analyze the hydrogeochemical origins of various groundwater. The Gibbs diagram is widely used to identify the natural mechanisms (rock weathering, precipitation, and evaporation) that affect the dissolved chemical constituents of surface water and groundwater (Gu et al, 2022;Bian et al, 2023). Based on Figures 5A, B, it can be observed that the majority of sampling points in the study area are distributed in the weathered rock zone and are far from the influence of atmospheric rainfall.…”
Section: Hydrochemical Characteristics Of Groundwatermentioning
confidence: 99%
“…Gibbs diagrams and rock end-member element ratio diagrams can be used to analyze the hydrogeochemical origins of various groundwater. The Gibbs diagram is widely used to identify the natural mechanisms (rock weathering, precipitation, and evaporation) that affect the dissolved chemical constituents of surface water and groundwater (Gu et al, 2022;Bian et al, 2023). Based on Figures 5A, B, it can be observed that the majority of sampling points in the study area are distributed in the weathered rock zone and are far from the influence of atmospheric rainfall.…”
Section: Hydrochemical Characteristics Of Groundwatermentioning
confidence: 99%
“…Hydrochemical and isotopic data can be used to reconstruct the flow paths and storage characteristics of springs [15,16]. Indeed, water-rock interactions result in a kind of natural dynamic fluid under the control of the environment and rock structure [17].…”
Section: Introductionmentioning
confidence: 99%